Photo-thermal effects in gold nanoparticles dispersed in thermotropic nematic liquid crystals1. Issue 31 (21st August 2015) - Pezzi, Luigia; De Sio, Luciano; Veltri, Alessandro; Placido, Tiziana; Palermo, Giovanna; Comparelli, Roberto; Curri, Maria Lucia; Agostiano, Angela; Tabiryan, Nelson; Umeton, Cesare
<x xml:space="preserve">Abstract</x> Investigation of nanoscale heat transfer in anisotropic media by combining the plasmonic properties of gold nanoparticles and the thermosensitivity of liquid crystals.